Intratumoral androgen biosynthesis in prostate cancer: Evidence from preclinical models and clinical specimens - Knuuttila, Matias (fi=Turun yliopisto|en=University of Turku|, 2017)
Androgens regulate the growth and development of normal prostate and prostate cancer. Blocking the production and effects of androgens, either by castration or medication, has been the most efficient strategy for treating metastatic prostate cancer for decades. Although most patients respond to the therapy, in many of them the disease progresses to castration-resistant prostate cancer (CRPC) that cannot be cured with current therapies. Intratumoral androgen biosynthesis has been identified as one of the mechanisms leading to castration resistance. Recent studies have confirmed that prostate tumors can synthesize androgens by themselves to maintain tumor growth in androgen-deprived conditions. Thus, suppressing intratumoral androgen biosynthesis has become an attractive option for drug development. To understand the mechanisms of intratumoral androgen biosynthesis and develop new CRPC therapies, better preclinical models for CRPC are needed. In this study, we developed an orthotopic VCaP xenograft model suitable for studying the progression of CRPC and the mechanisms of intratumoral androgen biosynthesis in vivo. The VCaP model exhibited the clinical features of CRPC, including the activation of intratumoral androgen biosynthesis and the overexpression of androgen receptor (AR) and its splice variants. Furthermore, novel antiandrogens enzalutamide and ARN-509 reduced intratumoral androgen levels and altered steroidogenic enzyme expression in the VCaP model. In addition to preclinical studies, androgen levels were analyzed in prostate and serum specimens obtained from prostate cancer patients. Intraprostatic androgen levels in cancerous and benign samples were highly variable between the patients. Distinct intratumoral androgen levels and altered AR target gene expression were associated with TMPRSS2-ERG fusion gene expression.